Evaluation of maxillary sinus septa using cone-beam computed tomography in a Turkish population - Guler, Ridvan; Gulsun, Belgin (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: A comprehensive understanding of maxillary sinus anatomy is essential for successful maxillofacial surgical interventions. The presence of bony septa along the inner surface of the sinus significantly increases the risk of Schneiderian membrane perforation during sinus floor elevation procedures for dental implant placement. Purpose: This study aimed to evaluate the frequency, localization, and lateralization of maxillary sinus septa using cone-beam computed tomography (CBCT) prior to sinus surgery. Methods: Cone-beam computed tomography images of 750 patients (353 men, 397 women) were included in this study. Cases with sinus septa were analyzed based on gender, anatomical location (anterior, middle, posterior), and lateralization (unilateral or bilateral). All data were recorded and statistically analyzed to determine prevalence rates. Results: The average age of the patients was 35 years. A total of 1,500 maxillary sinuses (right and left) were examined, and 275 sinus septa (32%) were identified in 240 patients. Of these, 60 septa (22%) were located in the anterior region, 140 (51%) in the middle, and 75 (27%) in the posterior region. Conclusion: In this study, sinus septa were present in 32% of patients in the Turkish population. Recognizing and detecting maxillary sinus septa with CBCT is important for preventing complications during surgical procedures.